2018
DOI: 10.1038/s41419-018-1054-3
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib-induced protective autophagy and apoptosis through the AKT–mTOR pathway in anaplastic thyroid cancer

Abstract: Apatinib, an inhibitor of vascular endothelial growth factor receptor-2, has been shown to promote anti-cancer action across a wide range of malignancies, including gastric, lung, and breast cancers. Our previous study showed that apatinib increases apoptosis in anaplastic thyroid carcinoma (ATC), but the direct functional mechanism of tumor lethality mediated by apatinib is still unknown. In this study, we demonstrated that apatinib induced both autophagy and apoptosis in human ATC cells through downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 50 publications
2
100
1
1
Order By: Relevance
“…In the present study, the combination of PLB and CDDP treatment induced autophagy, as evidenced by the accumulation of AVOs and autophagosomes as well as the upregulation of LC3-II, etc. The AKT/mTOR signaling pathway plays a key regulatory role in cell functions such as cell growth, apoptosis, and autophagy [39]. Our results showed that the PLB and CDDP cotreatment significantly inhibited the expression of p-AKT and p-mTOR, compared with either PLB and CDDP treatment alone.…”
mentioning
confidence: 55%
“…In the present study, the combination of PLB and CDDP treatment induced autophagy, as evidenced by the accumulation of AVOs and autophagosomes as well as the upregulation of LC3-II, etc. The AKT/mTOR signaling pathway plays a key regulatory role in cell functions such as cell growth, apoptosis, and autophagy [39]. Our results showed that the PLB and CDDP cotreatment significantly inhibited the expression of p-AKT and p-mTOR, compared with either PLB and CDDP treatment alone.…”
mentioning
confidence: 55%
“…Feng H et al con rmed that Akt/mTOR signaling pathway participate in the inhibition of autophagy and apoptosis at the same time 22 . Huo JF et al con rmed that the overexpression of GAS5 can enhance the cell sensitivity to cisplatin by inhibiting the excessive autophagy and this effect is achieved by regulating the expression of mTOR 23 . In the present study,the results showed that the level of miR-144 decreased,the level of mTOR increased and the autophagy level decreased after up-regulating the expression of GAS5, while the level of autophagy increased after upregulating GAS5 and adding mTOR inhibitor GDC-0349, suggesting that GDC-0349 can reverse the inhibition effect of GAS5 on autophagy after up regulating mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of mTOR and Akt is a key signaling step for the initiation of autophagy (30,31). To gain an insight into the signaling for BZA-induced autophagy, we determined the phosphorylation of mTOR, Akt, ULK, AMPK, and STAT3.…”
Section: Bza-induced Autophagy Is Associated With Ros Production Andmentioning
confidence: 99%